Rural Banking : The Case of Rural and Community Banks in Ghana - Nair, Ajai (World Bank, Washington, DC, 2017)
This case study describes the history and business model of the Rural and Community Bank (RCB) network in Ghana, analyzes its performance, identifies key issues, and makes recommendations on the way forward. The study analyzes the service delivery and financial performance of the RCBs. Before the establishment of RCBs in the late 1970s and the subsequent expansion of other service providers into rural areas, access to institutional credit for farm and nonfarm activities was scarce. The main sources of credit were moneylenders and traders that charged very high interest rates. In many rural communities, secure, safe, and convenient savings and payment facilities hardly existed. The first RCB was established in a farming community in the central region of Ghana in 1976. Rural communities showed tremendous interested in the community ownership and management features of RCBs, and by 1984 the number of RCBs reached 106. The introduction of a check payment system for cocoa farmers also spurred the establishment of local banks in many communities. The financial performance of many RCBs started to decline, however, for several reasons, including a drought that affected the country in 1983, weak governing ability, conflicts within boards of directors, and ineffective management in many RCBs. By the end of 2008, 127 RCBs were in operation with a total 584 service outlets. RCBs are regulated by Ghana's central bank, the Bank of Ghana, and thereby form part of the country's regulated financial sector. RCBs are the largest providers of formal financial services in rural areas and represent about half of the total banking outlets in Ghana.